SPECIFICS OF LEGAL ASSISTANCE UNDER AN AGREEMENT OF LEGAL AID CONCLUDED BY AN ATTORNEY - Khakimova Kamola (Scholar Express Journals, 2022)
This article is devoted to the study of legal aid by various subjects. The author analyzes the criteria for legal aid provided within the framework of a legal aid agreement, as well as the correlation of legal services as part of the aid. The question of the limits of the lawyer's liability for low-quality legal aid and the solution is considered.
Keywords: Qualified legal aid; legal services; notary; attorney